2011
DOI: 10.1523/jneurosci.5759-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Recruitment of Fast Amino Acid and Slow Neuropeptide Neurotransmitter Release Controls Gonadotropin-Releasing Hormone Neuron Excitability

Abstract: The anteroventral periventricular nucleus (AVPV) is thought to play a key role in regulating the excitability of gonadotropin-releasing hormone (GnRH) neurons that control fertility. Using an angled, parahorizontal brain slice preparation we have undertaken a series of electrophysiological experiments to examine how the AVPV controls GnRH neurons in adult male and female mice. More than half (59%) of GnRH neurons located in the rostral preoptic area were found to receive monosynaptic inputs from the AVPV in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 47 publications
(64 reference statements)
8
128
2
Order By: Relevance
“…Studies over the last decade have focused intensely, if not exclusively, upon the roles of ESR1-expressing kisspeptin neurons in these feedback loops. Whereas a strong case can been made for ESR1-expressing kisspeptin neurons located in the rostral periventricular area of the third ventricle (RP3V) to be involved in the positive feedback mechanism Ohkura et al, 2009;Smith, 2013), the roles of ESR1-positive kisspeptin neurons in the arcuate nucleus (ARN) remain unclear (de Croft et al, 2012;Dubois et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies over the last decade have focused intensely, if not exclusively, upon the roles of ESR1-expressing kisspeptin neurons in these feedback loops. Whereas a strong case can been made for ESR1-expressing kisspeptin neurons located in the rostral periventricular area of the third ventricle (RP3V) to be involved in the positive feedback mechanism Ohkura et al, 2009;Smith, 2013), the roles of ESR1-positive kisspeptin neurons in the arcuate nucleus (ARN) remain unclear (de Croft et al, 2012;Dubois et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…VGLUT2 is the glutamate transporter used by all glutamatergic neurons in the hypothalamus, thalamus, midbrain, and hindbrain (Takamori, 2006), whereas all GABAergic neurons express VGAT (Wojcik et al, 2006). Both the Vgat-ires-Cre and Vglut2-ires-Cre knock-in mouse lines have been fully characterized and shown to express Cre selectively in GABAergic and glutamatergic neurons, respectively (Vong et al, 2011). To fluorescently label GABAergic and glutamatergic neurons, the different Cre driver lines were crossed with the Ai9 Cre-dependent tdTomato reporter (Madisen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the suppression of testosterone was apparently faster and more pronounced, and reproductive organ weights more reduced than after administration of the GnRH analogue, Leuprolide. This result is unexpected as kisspeptin stimulation of LH in humans and a number of animal studies is much less than that of GnRH and kisspeptin antagonists, and only partially suppresses LH, suggesting that there is an element of GnRH secretion which is kisspeptin independent 110,114 .…”
Section: Kp Peptide Agonist and Antagonist Analoguesmentioning
confidence: 94%
“…Such a system is reminiscent of the relay neurons in the sacrococcygeal spinal cord that were previously suggested to drive lumbar rhythms. 10 On the other hand, previous studies have shown that stimulation frequency might sculpt circuit synapses through different plasticity mechanisms: modifying either the amount 16 or type 17 of released neurotransmitters, reversing the balance between excitation and inhibition, 18 or limiting negative-feedback pre-synaptic processes. 19 In addition, circuit architecture can be flexibly reconfigured by distinct stimulation frequencies.…”
Section: Frequency Of Incoming Inputs Is More Important Than Intensitymentioning
confidence: 99%